Gothic architecture and sexuality in the circle of Horace Walpole - Reeve, Matthew M. (The Pennsylvania State University Press, 2020)
"Addresses the question of how and why Horace Walpole and the men of his circle promoted the Gothic style in art, architecture, and literature in the latter half of the eighteenth century"--